The Effectiveness of The Child Protection Law in Addressing Bullying in Educational Settings - R. Leni Murzaini; Noenik Soekorini; Dedi Wardana Nasution; Fitri Ayuningtyas (Eduvest - Journal of Universal Studies, 2026)
This study aims to normatively analyze the effectiveness of The Effectiveness of the Child Protection Law in Addressing Bullying in Educational Settings in preventing and addressing bullying within educational environments. The research focuses on the legal framework stipulated in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 on Child Protection, Law Number 20 of 2003 on the National Education System, Law Number 11 of 2012 on the Juvenile Criminal Justice System, and other related regulations governing the protection of children from physical, psychological, verbal, and digital violence in educational institutions. This study employs normative legal research methods using statutory, conceptual, and case approaches. The findings indicate that the Child Protection Law provides a strong normative legal foundation to guarantee children’s rights to protection from all forms of violence, discrimination, and bullying in educational settings. However, its practical effectiveness remains constrained by several challenges, including weak institutional supervision, inadequate reporting mechanisms, limited anti-bullying education, and insufficient coordination among schools, parents, and law enforcement authorities. These obstacles often result in suboptimal handling of bullying cases, thereby failing to ensure maximum protection for victims and appropriate rehabilitation for child offenders. This study concludes that strengthening legal implementation requires policy harmonization, enhanced institutional oversight, preventive educational strategies, and law enforcement approaches that prioritize child protection and the best interests of the child within educational environments. Such measures are essential to ensure a safer and more legally protected educational system for children in Indonesia.